Given two sequences,
$$
u=\sum_{i=0}^{n-1}{u_i2^{ip}},\ u_i\in \mathbb{Z},\ p\ is\ prime
$$
$$
v=\sum_{i=0}^{n-1}{v_i2^{ip}},\ v_i\in \mathbb{Z},\ p\ is\ prime
$$
If we interchange two positions in sequence $u$ at positions $k, l$, such that $k>l$. All other elements in the two sequences in $u$ and in $v$ are same except the one interchanged at $k, l$ of sequence $u$. Then if we subtract the two sequences, $u-v = (u_k2^{pk}+u_l2^{pl})-(v_k2^{pk}+v_l2^{pl})$. Any hint please here?
I know that since all other terms are similar, then they get cancellled from $u,v$, but how we got as result …